Climate-growth relationships of Norway spruce beyond its natural distribution range - Frigo, Davide (2022)
The aim of this thesis is to study, using dendrochronological techniques, the growth response to climate of Norway spruce (Picea abies) beyond its natural distribution. The work has been conducted in Iceland, to see how the species is behaving beyond its current northern natural range; moreover, further Norway spruce samples have been collected in two plantations in Marche and Emilia Romagna Regions, Central Italy, to study species’ growth trends in correspondence of the southern distribution limit and beyond it. In order to better understand growth dynamics within the Icelandic sites, we also collected more samples from two other tree species, Picea sitchensis (Sitka spruce) and Pinus contorta (lodgepole pine). The analysis of the radial increment of the trees showed an overall high fluctuation in the tree ring width, beginning in the 1990s both in Italian and Icelandic sites. This pattern is maybe related to climate, testifying an increase of hot and dry summers in the last thirty years. Moreover, the climate-growth correlation profiles highlighted a diverse action of climate on tree growth, which seems to vary according to latitude: at northern latitudes, within the Icelandic sites, Norway spruce growth is mainly affected by temperatures, especially mean summer temperature (June July and August), whereas, towards southern latitudes, within the Italian sites, precipitation regime plays a major role on the species’ growth, especially during July of the current year and June of the previous year. The Emilia Romagna site showed an overall low correlation with climate, probably due to the shortness of available data. Sitka spruce and lodgepole pine climate-growth relationships proved useful to better understand growth patterns in Iceland, supporting the growth trend showed by Norway spruce. Considering the present warming climate scenario and the general uncertainties on tree migration and growth patterns, these results can contribute for a better understanding on the growth of the species outside its distribution ...